Improving Community Social Relationships through Education and Competition Activities in Timbang Lawan Village - Imsar ,M.S; Rifaldi Dwi Syahputra; Syakira Rifdhayani Yoes; Putri Khairani Pratiwi; Ogi Rahmadana (Universitas Muhammadiyah Enrekang, 2023)
The research that has been conducted is entitled